2000
DOI: 10.1097/00005537-200006000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on Motor Units in the Human Thyroarytenoid Muscle

Abstract: Objectives: To determine whether age differences are present in the human laryngeal thyroarytenoid muscle that would indicate that different normative values would be needed for identifying motor unit abnormalities. Study Design: Twenty-six consecutively recruited healthy subjects between the ages of 21 and 72 years participated in a laryngeal electromyography study. Methods: Bipolar needle electrodes were used to record motor unit action potentials from several locations in the right and left thyroarytenoid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 42 publications
3
46
2
Order By: Relevance
“…Ageing has effects on the voice and movement of the person and thereby, aged voice is characterized by some specific features such as imprecise production of consonants, tremors, hesitations and slower articulation [52]. Some studies have shown age-related degeneration with atrophy of vocal cords, calcification of laryngeal cartilages, and changes in muscles of larynx [53] [58] made a very useful and interesting longitudinal study by using records of defence speech delivered in the Supreme Court of the United States over a decade by the same judges. This study showed that an adaptation to each speaker can get closer to the scores of non-aged speakers but this implies that the ASR must be adapted to each speaker.…”
Section: Smart Home and Aalmentioning
confidence: 99%
“…Ageing has effects on the voice and movement of the person and thereby, aged voice is characterized by some specific features such as imprecise production of consonants, tremors, hesitations and slower articulation [52]. Some studies have shown age-related degeneration with atrophy of vocal cords, calcification of laryngeal cartilages, and changes in muscles of larynx [53] [58] made a very useful and interesting longitudinal study by using records of defence speech delivered in the Supreme Court of the United States over a decade by the same judges. This study showed that an adaptation to each speaker can get closer to the scores of non-aged speakers but this implies that the ASR must be adapted to each speaker.…”
Section: Smart Home and Aalmentioning
confidence: 99%
“…However, one of the main challenges to overcome for successful integration of VUIs is the adaptation of the system to elderly. From an anatomical point of view, some studies have shown age-related degeneration with atrophy of vocal cords, calcification of laryngeal cartilages, and changes in muscles of larynx [32] [24]. Thus, ageing voice is characterized by some specific features such as imprecise production of consonants, tremors and slower articulation [29].…”
Section: Information and Communication Technology (Ict)mentioning
confidence: 99%
“…From an anatomical point of view, studies have shown agerelated degeneration with atrophy of the vocal cords, calcification of the laryngeal cartilages, and changes in the muscles of the larynx 12,13 . Given that most acoustic models of ASR systems are trained from non-aged voice samples, they are not adequate to deal with more aged population and then classical ASR systems exhibit poor performances 14,15,16 .…”
Section: Ageing Voicementioning
confidence: 99%